2021
DOI: 10.3390/fishes6040047
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of Black Sea Bream (Acanthopagrus schlegelii) Stock Enhancement in the South China Sea Based on Microsatellite DNA Markers

Abstract: This is the first genetic evaluation of hatchery-based stock enhancement of black sea bream (Acanthopagrus schlegelii) in the South China Sea after a two-year monitoring period. In this study, microsatellite DNA markers were used to calculate the contribution rate and analyze genetic changes before and after stock enhancement. Two out of one hundred and sixty nine individuals from three recaptured populations were assigned to broodstock with a contribution rate of 1.18%, revealing that the hatchery-released ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…But our results of Hardy-Weinberg equilibrium test is not significant, so we can not confirm the existence of inbreeding or the deficiency of heterozygotes in E. awoara's populations. In some previous studies, we found that marine fish populations off the coast of mainland China generally showed a slight heterozygote deficiency [20,76,77], which might be related to the reduction in effective population size caused by overfishing and the imbalance in the sex ratio [79].…”
Section: Genetic Diversitymentioning
confidence: 86%
See 1 more Smart Citation
“…But our results of Hardy-Weinberg equilibrium test is not significant, so we can not confirm the existence of inbreeding or the deficiency of heterozygotes in E. awoara's populations. In some previous studies, we found that marine fish populations off the coast of mainland China generally showed a slight heterozygote deficiency [20,76,77], which might be related to the reduction in effective population size caused by overfishing and the imbalance in the sex ratio [79].…”
Section: Genetic Diversitymentioning
confidence: 86%
“…Microsatellite DNA is an allelic genotype pattern and has a high mutation rate, so it is more suitable for monitoring population structure at present. Our study showed that the average number of alleles (Na) in four populations of E. awoara ranged from 13.4 (BBW) to 20.3 (MB), which was generally higher than that of other marine fishes in the coastal areas of mainland China (Lepturacanthus savala (Na = 10.3~14.0) [75]; Scombridae (Na = 7.455~8.818) [76]; L. polyactis (Na = 10.43~13.71) [20]; Acanthopagrus schlegelii (Na = 5.43~8.00) [77]; Sebastiscus marmoratus (Na = 2~12) [78]), which showed high genetic diversity. We also found that the expected heterozygosity of the four populations was higher than the observed heterozygosity, and the F IS value was positive, showing a deficiency of heterozygotes.…”
Section: Genetic Diversitymentioning
confidence: 92%
“…In the fry culture period, 150% of the water was changed, and net drawing and capture were conducted once. Generally, the radius of fry transportation was 500 m (D. S. Li, 1993; J. Li, 2020; J. K. Liu & He, 1992; Wang, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…To produce 1 kg of grass carp culture, approximately 3 m 3 of water is required, which involves emptying the pond once and emptying ~20%–30% of the pond 6–7 times. The grass carp are fed with green fodder and formula feed was 1:1 (weight ratio), and the feed coefficient of the adult grass carp culture stage was 1.6–1.89 (J. L. Li, 2020; Lin et al, 2006; J. K. Liu & He, 1992; Wang, 2000). The 80:20 modes (i.e., stocking 80% grass carp and 20% bighead carp and silver carp) were used in the adult culture stage (Gui et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Microsatellite DNA polymorphism evaluation of hatchery-based stock enhancement of black sea bream, Acanthopagrus schlegelii , in the South China Sea revealed the significant genetic differentiation of enhanced populations from native populations and the lower genetic diversity of the recaptured released groups of individuals [ 308 ]. It has been concluded that the release of cultured juveniles with lowered genetic quality is potentially harmful to the conservation of wild genotypes in native populations.…”
Section: Stocking Effects and Restoration Of Wild Populationsmentioning
confidence: 99%